2009
DOI: 10.1111/j.1746-1561.2008.00375.x
|View full text |Cite
|
Sign up to set email alerts
|

School Injury Among Ottawa‐Area Children: A Population‐Based Study

Abstract: Many children get hurt at school, particularly during informal recreation activities. Environmental modification and increased supervision are strategies that may reduce school injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
3
10
0
Order By: Relevance
“…The study findings align with international literature and suggest that boys sustain more school injuries than girls of similar age groups [9,11,15]. Boys have a significantly higher injury rate for all mechanisms of injury with the exception of injuries sustained while walking, and injuries occurring in sports areas.…”
Section: Plos Onesupporting
confidence: 87%
See 1 more Smart Citation
“…The study findings align with international literature and suggest that boys sustain more school injuries than girls of similar age groups [9,11,15]. Boys have a significantly higher injury rate for all mechanisms of injury with the exception of injuries sustained while walking, and injuries occurring in sports areas.…”
Section: Plos Onesupporting
confidence: 87%
“…School-related injury is a major contributor to paediatric-related emergency department visits and hospital admissions; where the majority of the reported injuries were bruises, sprain/strains, and open wounds to the upper extremities, lower extremities and head, overwhelmingly sustained by boys, and mostly occurring during organized sports and recreational activities [5][6][7][8][9][10]. Injury studies conducted in the United States and Canada confirmed that school injuries accounted for almost 10 to 20% of the overall burden of child injury, costing billions of dollars in hospitalizations and other estimated health care expenditures [3,6,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The summer peak in injury mortality in Japanese children and adolescents aged 0-19 years contrasts, however, with the finding of an earlier study from Canada which showed that there was an autumn peak in school injuries among children aged 5-19 years in 2002. In that study, the higher level of mortality in autumn was attributed to it being the most suitable season to undertake activities in school playgrounds in Canada [16]. In Japan, however, activities for children such as swimming in rivers and the sea or going on trips and school outings tend to mostly occur in summer [17] which might increase the subsequent risk of injury and possible death.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental modification and increased supervision can reduce school injuries (44). However, increased teacher supervision not necessarily help to prevent injuries, as 88% of injuries at Missouri schools, for instance, occurred while pupils were allegedly supervised by adults.…”
Section: Discussionmentioning
confidence: 99%